Implementation of Radio Frequency Identification (RFID) for Effective Financial Transactions - Akbar, Febiadi Wisnu; Setiawan, Tri Agus; Amalia, Nurul (Journal of Artificial Intelligence and Software Engineering, 2025)
The use of Radio Frequency Identification (RFID) technology has been widely used in various fields and offers great potential to be applied in various activities, including in financial transaction systems. This study aims to apply RFID as an efficient, safe, and practical payment method. The research method used is literature study, development of a prototype of an RFID-based payment transaction system with stages of collecting and analyzing requirements, rapid design, building a prototype, user evaluation, refining the prototype, and implementing and maintaining the product. The testing uses a white box, black box and UAT. The results of the study show that the use of RFID can increase the effectiveness of financial transactions compared to conventional methods, with increased security levels through data encryption. In addition, this technology allows for reduced queues and improved user experience in electronic payment systems.